The constitutive instruments of the internationalization of human rights - Morawska, Elżbieta Hanna (Polski Przegląd Stosunków Międzynarodowych, 2018)
he article deals with some aspects of the process of the internationalization of human rights. The analysis essentially covers the question of two international documents: the United Nations Charter (UN Charter) and the Universal Declaration of Human Rights (the Declaration). The article underlines that the UN Charter is generally considered a special treaty. Being a treaty that constitutes the UN, it is perceived both as the fundamental anchoring of the obligations of the States in the sphere of international law, and as such is recognized as an international quasi-constitution. Meanwhile, the human rights clauses contained in the UN Charter set the stage in the process of institutionalizing human rights within international law and, consequently, establishing a new branch of international law, i.e. international human rights law. The greater part of the article is dedicated to the Universal Declaration of Human Rights as a universal milestone in the process of internationalization of human rights. The article refers to debates on its philosophical roots, and above all its legal nature. The article highlights the evolution of doctrine and international jurisprudence in the latter area. At the same time, it shows a specific search – contrary to the explicit intent of the authors – to justify the legally binding nature of the Declaration.